2019
DOI: 10.1063/1.5078674
|View full text |Cite
|
Sign up to set email alerts
|

Role of buoyancy-driven vortices in inducing different modes of coupled behaviour in candle-flame oscillators

Abstract: We investigate the coupled behaviour of two oscillatory flames produced by separate bundles of candles, referred to as candle-flame oscillators, as the distance between them is varied. Each bundle consists of four candles whose individual flames are fused so that the resultant flame produces self-sustained limit cycle oscillations. The recent study by Manoj et al. [Scientific Reports 8, 11626 (2018)] has reported the occurrence of four different modes of coupled behaviour, which include in-phase synchronizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A more reasonable conjecture was given by Nakamura et al [26] that the viscosity suppresses the hydrodynamic disturbance and leads to the mode transition of double flickering jet flames. It is worth mentioning that Dange et al [56] recently provided a direct experimental support to our hypothesis [57] that the mode transition is determined by the interactions between the buoyancyinduced vortices. In this section, we shall focus on quantifying the interaction between the inner-side shear layers of the two different flames to reveal the nature of the transition between the two flickering modes.…”
Section: Criterion For Flickering Mode Transitionsupporting
confidence: 73%
See 1 more Smart Citation
“…A more reasonable conjecture was given by Nakamura et al [26] that the viscosity suppresses the hydrodynamic disturbance and leads to the mode transition of double flickering jet flames. It is worth mentioning that Dange et al [56] recently provided a direct experimental support to our hypothesis [57] that the mode transition is determined by the interactions between the buoyancyinduced vortices. In this section, we shall focus on quantifying the interaction between the inner-side shear layers of the two different flames to reveal the nature of the transition between the two flickering modes.…”
Section: Criterion For Flickering Mode Transitionsupporting
confidence: 73%
“…Another interesting observation is the flame interaction mode of Fig. 11(e), which is termed the "amplitude death" mode [56] meaning no flickering.…”
Section: Further Validation and Discussionmentioning
confidence: 99%
“…When the link distance between the oscillators is d = 3, the neighbouring oscillators have a tendency to exhibit anti-phase synchrony. According to Dange et al [34], anti-phase synchrony is observed between the oscillators at d = 3 due to the alternate shedding of vortices from neighboring oscillators. If the number of oscillators in a network is even, there exists a global synchrony, in the form of clustering, between the oscillators, where the neighbouring oscillators are locked at 180 degrees of phase shift and alternate oscillators are locked at 0 degrees of phase shift.…”
Section: Resultsmentioning
confidence: 97%
“…If two diffusion flames are placed nearby each other collective behaviour in form of synchronization of the flickering can appear. [5,7,9,[19][20][21][22][23]. Similarly with the studies performed on candle flames, first we will examine the collective oscillation frequency and the synchronization order parameter z for two Helium columns with the same flow parameters (yield and nozzle diameter) as a function of the distance between the nozzles.…”
Section: Collective Behaviourmentioning
confidence: 99%